Protocol for the microinjection of free fatty acids and triacylglycerol in zebrafish embryos - Bridget Konadu; Carol K. Cox; Yann Gibert (STAR Protocols, 2024)
Summary: During development, the zebrafish embryo relies on its yolk sac as a nutrient source. Here, we present a protocol for modifying the free fatty acid (FFA) and triacylglycerol (TAG) content of the zebrafish yolk sac by microinjection. We describe steps for needle and injection mold preparation, FFA and TAG solution preparation, and microinjection. This protocol can elucidate how excesses of FFA and TAG affect development and modify the transcriptome of zebrafish embryos.For complete details on the use and execution of this protocol, please refer to Konadu et al. 1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.